Estudio comparativo del control de malezas postemergente dirigido y no dirigido en el cultivo de pimiento (Capsicum annuum) - Castro Saltos, Christian Héctor (2015)
This research was conducted at the site of the experimental farm "San Pablo" of the Faculty of Agricultural Sciences at the Technical University of Babahoyo, Los Rios province; located at kilometer 7.5 of the road Babahoyo - Montalvo, whose coordinates are 1 47' 50.478 "south latitude and 79 ° 29' 0.5856" west longitude at an altitude of 8 meters. The area is characterized by an average temperature of 25.5 0C, relative humidity of 78.7% and annual rainfall of 2100 mm. The floor is flat topography, silt loam texture and regulate drainage. The aim of this study was to identify the appropriate herbicide treatment in the cultivation of pepper, to evaluate the effect of herbicides on weeds of wide and narrow leaf pepper growing and economically analyze the results. As the material is planted pepper seeds long Irazu variety was used; the treatments were Oxyfluorfen (1.5 L / ha) Paraquat (2.0 L / ha), Diquat (2.0 L / ha) and directed postemergence Propaquizofop (1.0 L / ha), Quizalofop (herbicides 1.0 L / ha), Fenoxaprop (1.0 L / ha) postemergence not directed more a mechanical control with three manual weeding and three repetitions; experimental design randomized complete blocks with Duncan Multiple Test Range at 5% probability was used. All agricultural practices applied in the cultivation and seedbed preparation, transplanting, weeding, watering, fertilizing, controlling insect pests and crop were made..........